Linear Versus Nonlinear Methods for Detecting Magnetospheric and Ionospheric Current Systems Patterns. Issue 7 (27th July 2020) - Alberti, T.; Giannattasio, F.; De Michelis, P.; Consolini, G.
Abstract: There is a growing interest in the development of models and methods of analysis aimed to recognize in the geomagnetic field signals the different contributions coming from the various sources both internal and external to the Earth. Many models describing the geomagnetic field of internal and external origin have been developed. Here, we investigate the possibility to recognize in the magnetic field of external origin the different contributions coming from external sources. We consider the measurements of the vertical component of the geomagnetic field recorded by the European Space Agency (ESA) Swarm A and B satellites at low and mid latitudes during a geomagnetically quiet period. We apply two different methods of analysis: a linear method, that is, the empirical orthogonal function (EOF), and a nonlinear one, that is, the multivariate empirical mode decomposition (MEMD). Due to the high nonlinear behavior of the different external contributions to the magnetic signal the MEMD seems to recognize better than EOF the main intrinsic modes capable of describing the different magnetic spatial structures embedded in the analyzed signal. By applying the MEMD only five modes and a residue are necessary to recognize the different contributions coming from the external sources in the magnetic signal against the 26 modes that are necessary in the case of the EOF. This study is an example of the potential of the MEMD to give new insights into the analysis of the geomagnetic field of external origin and to separate the ionospheric signal from the magnetospheric one in a simple and rapid way. Key Points: Both linear and nonlinear methods are used to investigate magnetic field patterns obtained by Swarm data The EOF analysis does not allow extraction of nonoscillating components The MEMD allows detection of both oscillating (of ionospheric origin) and nonoscillating (of magnetospheric origin) contributions